2015
DOI: 10.1039/c5cp00804b
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of monodisperse α-calcium sulfate hemihydrate nanoellipsoids with a porous structure

Abstract: We report a facile and green chemical solution approach to synthesize monodisperse α-calcium sulfate hemihydrate (α-HH) nanoellipsoids with a length of 600 nm and a width of 300 nm by simply mixing Ca(2+) and SO4(2-) glycerol-water precursor solutions in the presence of Na2EDTA. The α-HH nanoellipsoid is formed through a Na2EDTA-mediated self-assembly of small primary building blocks (α-HH domains: ∼14 nm). The study on the morphological evolution of α-HH reveals that the controlled synergy of supersaturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
(29 reference statements)
1
21
0
Order By: Relevance
“…The crystal lattice of α-HH consists of -Ca-SO 4 -Ca-SO 4 -Ca-chains with repeating, ionically bonded Ca and SO 4 ions, which forms a framework with continuous channels parallel to the c axis and favors the preferential 1D growth along the c axis. 15 In general, as the Na 2 EDTA concentration is raised, the monodispersity and smoothness of α-HH polycrystalline microspheres get better and then deteriorate. The crystallization process changes upon the addition of Na 2 EDTA.…”
Section: Effect Of Na 2 Edtamentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal lattice of α-HH consists of -Ca-SO 4 -Ca-SO 4 -Ca-chains with repeating, ionically bonded Ca and SO 4 ions, which forms a framework with continuous channels parallel to the c axis and favors the preferential 1D growth along the c axis. 15 In general, as the Na 2 EDTA concentration is raised, the monodispersity and smoothness of α-HH polycrystalline microspheres get better and then deteriorate. The crystallization process changes upon the addition of Na 2 EDTA.…”
Section: Effect Of Na 2 Edtamentioning
confidence: 99%
“…4,11 The structure, morphology and size of α-HH often determine its properties and functionalities. 13,14 On the other hand, micro-scale α-HH single crystals are mainly used as ceramic molds, building materials and bone-substitute materials, while the nano-scale α-HH polycrystals can promisingly serve as drug carriers and find other medical applications, 15 thus highlighting the importance of structure and morphology control of α-HH. 12 In comparison, α-HH particles with a low aspect ratio or spherical shape possess better injectability and mechanical properties after hydration, and are preferable for use as bone cements.…”
Section: Introductionmentioning
confidence: 99%
“…5b, three adsorption peaks at 1584 cm À1 , 1404 cm À1 and 1385 cm À1 in the FT-IR spectrum of the obtained a-CaSO 4 $0.5H 2 O crystals (blue curve in Fig. 5b) should be assigned to the asymmetric and symmetric stretching vibrations of -COO-, 44,48 and the three peaks were all shied to lower wavenumbers as compared with those in the FT-IR spectrum of PT. This result indicated that tartrate ions from PT were absorbed on the surface of the obtained a-CaSO 4 $0.5H 2 O crystals.…”
Section: Resultsmentioning
confidence: 85%
“…2b) of the crystal showed that the observed d-spacing were 0.598 nm and 0.344 nm, closing to that for (002) and (020) facets of a-CaSO 4 $0.5H 2 O, respectively. 44 The XRD pattern of the as-prepared rod-shaped crystals was shown in Fig. 2c, and the main diffraction peaks at 14.91 , 25.61 , 26.82 , 29.77 and 31.52 were assigned to (200), (020), (À121), (400) and (204) facets of CaSO 4 $0.5H 2 O crystals (JCPDS 41-0224), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation